Changes in the rural economy in Bangladesh under COVID-19 lockdown measures: Evidence from a phone survey of Mahbub Hossain sample households - Mohammad Abdul Malek; Truong Thi Hoa; Tetsushi Sonobe (Asian Development Bank Institute (ADBI), 2021)
This study offers a comprehensive picture of the rural economy in Bangladesh during the first three months of the lockdown period in comparison with the pre-COVID-19 situation. Using a nationally representative sample (of 2,312 rural households from 62 villages in 56 districts) known as the Mahbub Hossain Survey sample, we conducted a telephone survey in June 2020. Our descriptive and regression analyses suggest that, during the survey period, the rural economy experienced several adverse impacts from the containment measures, such as a delayed harvest, difficulty in selling farm produce, labor and material input disruptions and cost increases, and reductions in remittance receipts and non-farm business sales. Rural households had to reduce their food consumption and receive food support from the government and cash support from the private sector. Vulnerability was especially apparent in households with a head who was female, less educated, young, or casual labor. Livelihoods varied significantly among geographical areas according to the concentration of the infection and less significantly according to the stringency of the lockdown measures. We also found that rural households preferred cash or product support, rural work or employment support, and cash assistance or soft loans for farm inputs and business inputs at the time of the survey.
Keywords: D10; I38; Q12; R20; 330; rural households; production economy; livelihoods; COVID-19 lockdown measures; Bangladesh